Foot peripheral sensory neuropathy: a frequent disabling manifestation in systemic sclerosis - Alcacer-Pitarch, Begonya; Di Battista, Marco; Redmond, Anthony C; Keenan, Anne-Maree; Di Donato, Stefano; Buch, Maya H; Del Galdo, Francesco (Rheumatology (Oxford, England), 2025)
Abstract Objectives Peripheral sensory neuropathy (PSN) is an under-recognized feature in SSc. Moreover, SSc foot involvement is frequent but poorly investigated. We aimed to provide a detailed characterization of foot PSN in a large cohort of SSc patients, describing its associations with disease-specific features, physical disability and quality of life (QoL). Methods SSc patients and healthy controls (HCs) comparable for age and gender were enrolled in a cross-sectional observational case-control study. All subjects underwent a detailed quantitative sensory testing of feet evaluating touch, vibratory, thermal and pain sensitivity, ultimately investigating the presence of large and small fiber neuropathy. Patient-reported outcomes (Scleroderma Health Assessment Questionnaire, Manchester Foot Pain and Disability Index and Systemic Sclerosis Quality of Life Questionnaire) were administered to assess neuropathic symptoms, foot disability and QoL. Results A total of 109 SSc patients (88.1% female, median age 59.0 years) and 51 HC were enrolled. SSc patients presented with a significant impairment in each sensory parameter assessed (P ≤ 0.01 for all). Foot PSN was present in 85.3% of the patients, with 80% having small fiber and 57% large fiber neuropathy, co-existing in 51.4% of the cases. PSN was associated with age, smoking, foot ulceration, disease duration and corticosteroids use. Precisely, 80.6% subjects with PSN reported at least one neuropathic symptom. Patients with neuropathic symptoms reported worse physical function, worse foot disability and more impaired QoL. Conclusion Foot PSN presents as a common and disabling manifestation in SSc patients, involving small and large fibres. Hence, foot PSN assessment should be included as a part of the SSc workup.